Determinasi Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan - Prasetyo, Ary; Vicentius Ade Arianto Ciptoputra, Seriusman Zega, Merline Julianti, Suratman, (STIE AMKOP, 2024)
This study aims to determine the effect of organizational culture and work environment variables on employee performance variables. This type of research is explanatory research while the method used in this study is quantitative by using a questionnaire as a research instrument. The data collection technique in this study is using a simple random sampling technique with a sample size of 169 people from a total population of 292 employees at PT WIK Far East Batam. The analysis used in this study is the structural equality model (SEM) with Amos software version 24. The results of this study include organizational culture variables having a positive but insignificant effect on employee performance variables and work environment variables having a positive and significant effect on employee performance variables. The magnitude of the direct influence of organizational culture variables and work environment variables on employee performance variables is 55.1%.